The Ethical and the Metaphysical Will in the Early Wittgenstein (and Beyond) - Gómez-Alonso, Modesto (Analysis. Journal of Philosophical Research, 2021)
In the Notebooks 1914-1916, Wittgenstein engages himself in a dialogue with Schopenhauer’s project —one that Wittgenstein makes his own— of substituting an immanent metaphysics of human experience for the transcendent metaphysics discredited by Kant’s critique, and thus for finding a path that would be able both of capturing the reality of human agency and of staying away from the kind of self-alienation that appears to be the necessary consequence of philosophical reflection. Wittgenstein’s reflections on the ethical and the metaphysical will are instrumental to bring this project to successful completion. However, I will go well beyond Wittgenstein’s early work in order to elucidate what strikes me as the solution provided by the late Wittgenstein (mainly, in On Certainty) to two problems that the Notebooks and the Tractatus left unanswered. On the one hand, there is the question about whether the agreement between agency and passivity is possible—namely, about how to come to see the friction of the world not only as something that is, but rather as something that ought to be. On the other, there is the problem of how to make of ethical subjectivity and metaphysical subjectivity two constitutively co-related aspects of the same transcendental subjectivity.